Analysis of the Effect of the Increase in UMK and Fuel Prices on Trans Pakuan Bus Fee Corridor 2, Bogor City - Wibowo, Benny; Murtejo, Tedy; Alimuddin, Alimuddin (ASTONJADRO, 2026)
Economic growth and urban development are driving an increasing need for efficient and affordable public transportation. Bogor, as one of the capital's satellite cities, faces unique challenges in managing its mass transportation system. To address these challenges, the local government, in collaboration with relevant parties, operates a Bus Rapid Transit (BRT) service known as Bus Trans Pakuan. Corridor 2, the main route connecting strategic areas within Bogor, serves as a key route. Transportation is an essential part of people's lives. Transportation comes from the Latin word "trans" meaning across or on the other side, and "portare" meaning to carry or transport. Transportation is the activity of moving or conveying cargo (goods and people) from one place to another. However, along with economic dynamics, vehicle operating costs (BOK), including fuel costs (BBM) and the city minimum wage (UMK), have increased. Which stated that the increase in subsidized fuel prices resulted in inflation in the region, which could disrupt people's purchasing power, which ultimately led to an increase in household consumption expenditure, followed by an increase in the prices of other basic necessities. However, along with socioeconomic dynamics, several external factors can affect public transportation operating costs, one of which is the increase in the Regency/City Minimum Wage (UMK). The increase in the UMK directly impacts operational cost components, including driver salaries, operational staff, and other indirect costs. Furthermore, this factor also has the potential to put pressure on fuel (BBM) expenditures, a key component of bus operations.